RESEARCH-BASED KOLEGA LEARNING MODEL ON BIOLOGY TO GROW THE HABIT OF SCIENTIFIC LEARNING FOR SENIOR HIGH SCHOOL STUDENTS - Sasmito, Agung Probo (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This research is intended to discover (1) the influence of research-based KOLEGA (Kontrol Lembar Keluarga/Family Control Sheet) learning model’s implementation to grow students’ scientific learning habit and (2) the influence of KOLEGA model to improve students’ learning outcome. This research used experiment method with Pretest–Postest Control Group design. The subject of this research was students of XI MIPA Class of SMA Negeri 1 Lasem academic year 2016/ 2017. The data of the research were students’ scientific learning habit and their learning outcome. The data were collected from questionnaire, test, and documentation. The sample was taken with purposive sampling. The samples consist of two classes, the experiment class of XI MIPA 4, a class which has been known on having low average result of biology, and the control class of XI MIPA 5. The analysis of the data used descriptive quantitative. The result and discussions showed that: (1) the implementation of KOLEGA can grow students’ scientific learning habit. The measurement obtained the data of tcount = 291.028, while ttable = 2,045. Since tcount > ttable, it can be concluded that the implementation of the design can grow students’ scientific learning habit; (2) the implementatio of KOLEGA can increase students’ learning result. The experiment obtained the data of tcount = 2.037 and ttable = 1.671. Since tcount > ttable (2.037 > 1.671), therefore, Ho is rejected or Ha is accepted.